Going beyond the "inside-outside" dilemma? - Subirats Humet, Joan (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2015)
This article addresses a classic dilemma of social movements: whether to "enter" political institutions in order to gain a position of power and change reality in the desired direction, or just stay "outside". In Spain today, after more than seven years of crisis, and with a clear understanding of what “a change of era” means, the emergence of other political parties raises this issue from new points of view.  It is not a question of substituting the elite, worn out as a result of their collusion with economic powers and corruption, with a new one that will regenerate the same system. It is a question of assaulting the institutions from the public sphere and recovering them for the common good.  There is no guarantee that this process will succeed, or it will finally dissolve into nothing. But the size of the challenge remains.
Keywords: Assault; change; elites; Political Institutions; Podemos